Magneto-optical fiber sensor based on magnetic fluid - Zu, Peng (2013)
A novel magnetic field fiber sensor based on magnetic fluid is proposed. The sensor is configured as a Sagnac interferometer structure with a magnetic fluid film and a section of polarization maintaining fiber inserted into the fiber loop to produce a sinusoidal interference spectrum for measurement. The output interference spectrum is shifted as the change of the applied magnetic field strength with a sensitivity of 16.7 pm/Oe and a resolution of 0.60 Oe. The output optical power is varied with the change of the applied magnetic field strength with a sensitivity of 0.3998 dB/Oe.